Carbon steel biocorrosion at 80 °C by a thermophilic sulfate reducing archaeon biofilm provides evidence for its utilization of elemental iron as electron donor through extracellular electron transfer. (December 2018) - Jia, Ru; Yang, Dongqing; Xu, Dake; Gu, Tingyue
Highlights: Archaeoglobus fulgidus is a very corrosive sulfate reducing archaeon at 80 °C. Pre-grown A. fulgidus biofilm is more corrosive under carbon source starvation. Its corrosion type is extracellular electron transfer MIC (EET-MIC). This archaeon is capable of using elemental iron as an electron donor. Linear polarization resistance data support MIC weight loss and pit depth data. Abstract: Mature sulfate reducing archaeon ( Archaeoglobus fulgidus ) biofilm at 80 °C was found more corrosive against C1018 carbon steel under organic carbon starvation. After 3-day pre-growth in enriched artificial seawater medium (EASW), C1018 coupons with biofilms were placed in fresh EASW with reduced carbon source levels for an additional 7 days of incubation. Coupon weight losses were 0.9 mg/cm 2, 2.0 mg/cm 2 and 1.4 mg/cm 2 for this subsequent 7-day starvation period, corresponding to 0%, 90% and 100% carbon source reductions, respectively. Electrochemical tests corroborated the weight loss data, providing evidence for the utilization of elemental iron as electron donor through extracellular electron transfer.